Differential Impact of Child Sexual Abuse and Family History of Suicidal Behavior in High-Risk Suicidal Patients - Grendas, Leandro (2019)
The current study aimed to compare suicide-related variables as a function of 1) family history of suicidal behavior and 2) child sexual abuse among patients hospitalized for a suicide attempt or active suicidal ideation. Family history of suicidal behavior and child sexual abuse were examined independently and in combination as a diathesis for a high-risk suicidal phenotype. A multicenter cross-sectional study was designed to compare data obtained from 292 patients hospitalized for suicidal behavior. Demographic and clinical variables were compared among Group 1 (patients who reported both family history of suicidal behavior and child sexual abuse), Group 2 (patients who reported only family history of suicidal behavior), Group 3 (patients who reported only child sexual abuse), and Group 4 (patients who did not report family history of suicidal behavior or childhood sexual abuse). A multinomial logistic regression was used to examine suicide-related variables associated with each group and to compare differences between groups. Group 1 and 3 endorsed a higher number of previous suicide attempts and were more likely to be younger at the first suicide attempt compared to Group 4. Group differences remained after adjustment in a multinomial regression model. The current findings suggest that child sexual abuse may be more strongly related to suicide risk among high risk patients than family history of suicidal behavior.